2022
DOI: 10.3389/fimmu.2022.906275
|View full text |Cite
|
Sign up to set email alerts
|

6-Valent Virus-Like Particle-Based Vaccine Induced Potent and Sustained Immunity Against Noroviruses in Mice

Abstract: Norovirus is a major cause of acute gastroenteritis worldwide, and no vaccine is currently available. The genetic and antigenic diversity of Norovirus presents challenges for providing broad immune protection, which calls for a multivalent vaccine application. In this study, we investigated the possibility of developing a virus-like particle (VLP)-based 6-valent Norovirus vaccine candidate (Hexa-VLPs) that covers GI.1, GII.2, GII.3, GII.4, GII.6, and GII.17 genotypes. Hexa-VLPs (30 µg) adjuvanted with 500 µg o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Norovirus (Nov) is a single positive-stranded RNA virus that is currently the main viral pathogen causing acute gastroenteritis in most countries worldwide. , The norovirus genome is approximately 7500 nucleotides in length and consists of three open reading frames (ORFs). ORF2 encodes the major capsid protein VP1, , which assembles into 38–40 nm (180 subunits) or 23 nm (60 subunits) Nov VLPs after being expressed in Pichia pastoris expression systems , and baculovirus expression systems. , Interestingly, structural analysis of the Nov capsid via X-ray crystallography revealed that full-length VP1 consists of an N-terminal shell (S) domain connected by a short, flexible hinge to a C-terminus-protruding (P) domain . Structural proteins lacking the P domain can self-assemble into NPs with diameters slightly less than 30 nm, suggesting that the S domain alone shows the potential to present a protein antigen of interest in a nanoparticle structure .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Norovirus (Nov) is a single positive-stranded RNA virus that is currently the main viral pathogen causing acute gastroenteritis in most countries worldwide. , The norovirus genome is approximately 7500 nucleotides in length and consists of three open reading frames (ORFs). ORF2 encodes the major capsid protein VP1, , which assembles into 38–40 nm (180 subunits) or 23 nm (60 subunits) Nov VLPs after being expressed in Pichia pastoris expression systems , and baculovirus expression systems. , Interestingly, structural analysis of the Nov capsid via X-ray crystallography revealed that full-length VP1 consists of an N-terminal shell (S) domain connected by a short, flexible hinge to a C-terminus-protruding (P) domain . Structural proteins lacking the P domain can self-assemble into NPs with diameters slightly less than 30 nm, suggesting that the S domain alone shows the potential to present a protein antigen of interest in a nanoparticle structure .…”
Section: Introductionmentioning
confidence: 99%
“…20,21 The norovirus genome is approximately 7500 nucleotides in length and consists of three open reading frames (ORFs). ORF2 encodes the major capsid protein VP1, 22,23 which assembles into 38−40 nm (180 subunits) or 23 nm (60 subunits) Nov VLPs after being expressed in Pichia pastoris expression systems 24,25 and baculovirus expression systems. 26,27 Interestingly, structural analysis of the Nov capsid via X-ray crystallography revealed that full-length VP1 consists of an N-terminal shell (S) domain connected by a short, flexible hinge to a C-terminus-protruding (P) domain.…”
Section: Introductionmentioning
confidence: 99%
“…NVs belonging to the Caliciviridae family can be classified into 10 genogroups (GI–GX) and 48 genotypes [ 3 ]. Among the genogroups, GI, GII, GIV, GVIII, and GIX are known to infect humans, and the GII.4 genotype accounts for the majority of outbreaks worldwide [ 3 , 4 , 5 ]. Human norovirus (HuNV) initiates infection by binding to a receptor, histo-blood group antigen (HBGA), using the protruding (P) domain of the capsid protein VP1 [ 6 ].…”
Section: Introductionmentioning
confidence: 99%